2015
DOI: 10.5001/omj.2015.08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acne on Quality of Life of Students at Sultan Qaboos University

Abstract: This study showed that acne affects the quality of life of affected SQU students treated by primary care physicians at the Student Clinic. Therefore, physicians should take into account the effect of acne on the persons' quality of life when individualizing treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
3
13
1
Order By: Relevance
“…They think that gender doesn't effect acne quality of life [5]. However, Al-Shidhani, et al think that female patients are more negatively affected than males, as expected, according to their study [15]. The same results are seen in other studies [18][19][20][21].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…They think that gender doesn't effect acne quality of life [5]. However, Al-Shidhani, et al think that female patients are more negatively affected than males, as expected, according to their study [15]. The same results are seen in other studies [18][19][20][21].…”
Section: Discussionsupporting
confidence: 61%
“…SOCQOL isn't enough alone for the effects of acne severity. According to Al-Shidhani, et al any increase in acne severity would lead to an increase in the negative effects on the patients' feelings, self-perception, and socialization as the lesions became more prominent and if scarring occurred [15]. Few studies reported a significant relationship between the severity of acne and its effect on the patient's QoL [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…To www.jmscr.igmpublication.org Impact Factor (SJIF): 6.379 Index Copernicus Value: 79.54 ISSN (e)-2347-176x ISSN (p) 2455-0450 DOI: https://dx.doi.org/10.18535/jmscr/v6i10.104 measure the HRQoL in acne, a valid and reliable acne specific instrument such as Cardiff Acne Disability Index (CADI) is used. 4 HRQoL impairment of acne patients has been reported in studies from the United States 5 , Greece 6 , Oman 7 , Saudi Arabia 8 , Malaysia 9 , Ukraine 10 , Serbia 11 and Iran 12 . The new word "QUIMP" meaning "quality of life impairment" was recently proposed by Professor Finlay 13 ; and recommended by the "European Academy of Dermatology and Venereology Task Forces on Quality of Life and Patient Oriented Outcomes" for routine clinical and research use.…”
Section: Introductionmentioning
confidence: 94%
“…A research carried out in Saudi Arabia found an overall prevalence of 14.3% among female secondary school students [14]. Most of these studies have been conducted in secondary school or high school students, with very few conducted in college and university students [4,12,15]. Our study focused on finding the prevalence of acne in female medical college students.…”
Section: Discussionmentioning
confidence: 99%